La comicitat, la paròdia i aspectes anticlericals en alguns contes plaents catalans: La disputació d'en Buc ab son cavall i el Testament de Serradell de Vic. - ARTIGAS, MIQUEL MARCO (Scripta, 2013)
This work is a study of three aspects that define these stories Catalan medieval verse that critics have considered that could be classified as fables. These aspects, as already mentioned in the title, are the comedy, parody and anticlericalism. Other issues that have these pleasant stories are considered important and interesting are the analysis of the characters, the different meanings given by critics and other features such as manuscripts, autors, have also been studied in this study. Previously a brief introduction to the socio-political context of the time and the crisis that affected the clergy is presented.